2020
DOI: 10.3390/jcm9103086
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Virtual Reality for the Management of Anxiety and Pain in Dental Treatments: Systematic Review and Meta-Analysis

Abstract: (1) Background: Dental treatments often cause pain and anxiety in patients. Virtual reality (VR) is a novel procedure that can provide distraction during dental procedures or prepare patients to receive such type of treatments. This meta-analysis is the first to gather evidence on the effectiveness of VR on the reduction of pain (P) and dental anxiety (DA) in patients undergoing dental treatment, regardless of age. (2) Methods: MEDLINE, CENTRAL, PubMed, EMBASE, Wiley Library and Web of Science were searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In the past few decades, the emergence of digital therapeutics (DTx) aimed at the use of informatic tools to aid the diagnosis and therapy of various pathologies has led to the creation of many new therapeutic devices [18]. Recently, multiple meta-analyses have specifically supported the efficacy of virtual reality (VR) in several type of acute and chronic pain conditions [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the emergence of digital therapeutics (DTx) aimed at the use of informatic tools to aid the diagnosis and therapy of various pathologies has led to the creation of many new therapeutic devices [18]. Recently, multiple meta-analyses have specifically supported the efficacy of virtual reality (VR) in several type of acute and chronic pain conditions [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The VR distraction used nonintrusive methods; therefore, the children’s parents or caregivers have not been concerned that general anesthesia might affect intelligence and learning ability. The adverse effects on vision and hearing have not been reported in this study and literature [ 31 , 38 40 ]. Even with repeated dental treatments, parents and children are much more receptive to other methods.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, the HMD changes the perception of the surrounding environment. A meta-analysis showed that VR is a useful distraction method in pediatrics (Eijlers et al, 2019 ) and dental procedures (Lopez-Valverde et al, 2020 ). Klassen et al ( 2008 ) and Uman et al ( 2013 ) indicated that distraction techniques, including VR, should be used in any needle-related procedures in children.…”
Section: Discussionmentioning
confidence: 99%